The chemical and isotopic analysis of English forest glass - Meek, Andrew (2011)
Glass is one of several early modern industries where the development from small-scale workshop to large-scale industry offers a valuable insight into wider socio-economic trends. Previously, medieval and early modern forest (wood ash) glass has been studied using a range of analytical techniques. However, characterisations of production centres and exchange systems for forest glasses are difficult to verify, in part because very few examples of raw glass from furnace sites have been investigated. The necessity for an independent means of provenancing glass used in the study of exchange systems is clear.